Prioritizing DevOps Implementation Guidelines for Sustainable Software Projects - Muhammad Zohaib; Ahmed Alsanad; Areej Abdullah Alhogail (IEEE Access)
The DevOps paradigm is increasingly being adopted in the software industry. To achieve sustainable DevOps adoption, organizations need to transform their culture, embrace automation, implement measurement practices, and foster sharing of knowledge and information (referred to as CAMS). Implementing DevOps principles can be complex for software organizations. However, sustainable DevOps implementation can lead to the development of high-quality projects with a favorable return on investment. This evidence-based study aims to explore the guidelines for sustainable DevOps implementation as reported in both the literature and industry practices. By conducting a systematic literature review and questionnaire survey, we identified 48 guidelines for sustainable DevOps implementation. Furthermore, we developed a decision-making framework to assist practitioners in prioritizing these guidelines. The results indicate that culture, among the CAMS aspects, is the most crucial principle for sustainable DevOps implementation. The highest priority guidelines for sustainable DevOps implementation include: (i) fostering a collaborative culture with shared goals, (ii) assessing the organization’s readiness for a microservices architecture, and (iii) educating executives about the benefits of DevOps to gain resource and budget support. We believe that this comprehensive study will aid practitioners in understanding the core principles and guidelines for sustainable DevOps implementation.